PERAN MNC MENCEGAH PENCEMARAN LINGKUNGAN : STUDI KASUS EXXONMOBIL DI BLOK CEPU - Wandha Lucia Kertiyasa; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2018)
The emergence of public distrust of the oil and gas giant ExxonMobil Indnesian was proven by various accusations that were filed for environmental pollution by ExxonMobil. The accusation was filed because there were several cases which resulted in an increase of temperature, gas leakage, and other charge that threatened human security. The thought framework used in this study uses the theory of good governance, human security, and also the preacautionarry principle. This type of research is descriptive-explanatory with qualitative data analysis techniques through data collection of library techniques. This study provides results that ExxonMobil isn’t the cause of environmental damage carried out in the Cepu Block exploration area. Through the results of the PROPER obedience (Corporate Performance Rating Assessment Program) applied by the Government, CSR (Corporate Social Responsibility),  the implementation of the Operations Integrity Management System (OIMS) as a guide in doing business, and enviromental care efforts carried out by the company  was enough to dismiss these environmental pollution allegations.